2014
DOI: 10.1111/jfbc.12084
|View full text |Cite
|
Sign up to set email alerts
|

The Juice of Asparagus By-Product Exerts Hypoglycemic Activity in Streptozotocin-Induced Diabetic Rats

Abstract: The woody ends of asparagus (Asparagus officinalis L.) spears contain various bioactive substances. However, they are often discarded as by‐products. We extracted juice from recycled woody stems of asparagus (AJ) to investigate its hypoglycemic effect in a streptozotocin‐induced diabetic rat model. The diabetic rats showed significant decreased fasting serum glucose, glycosylated serum protein and malondialdehyde levels after 21 days of AJ treatment. Moreover, the oral glucose tolerance test revealed that AJ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…Fuentes‐Alventosa reported that high dietary fiber powder obtained from asparagus by‐product exhibited antioxidant activity, and found that saponin content ranged from 2.14 to 3.64 mg g −1 fiber . Wen Zhang extracted juice from recycled woody stems of asparagus and found that the juice showed hypolipidemic properties in hyperlipidemic mice …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuentes‐Alventosa reported that high dietary fiber powder obtained from asparagus by‐product exhibited antioxidant activity, and found that saponin content ranged from 2.14 to 3.64 mg g −1 fiber . Wen Zhang extracted juice from recycled woody stems of asparagus and found that the juice showed hypolipidemic properties in hyperlipidemic mice …”
Section: Introductionmentioning
confidence: 99%
“…2 Wen Zhang extracted juice from recycled woody stems of asparagus and found that the juice showed hypolipidemic properties in hyperlipidemic mice. 3 Drying is a preservation method widely used in the food industry, and drying is recognized as one of the most common and most energy-consuming food preservation methods. Different drying technologies have different characteristics and each drying technique has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…1.13 Received: January 04, 2020; accepted: January 04, 2021 (tăng cường chuyển hóa, xây dựng tế bào). Ngoài việc được sử dụng như nguồn rau xanh hàng ngày, măng tây còn được đánh giá rất cao về những lợi ích đối với sức khỏe như chống ung thư, chống oxi hóa, giảm lipid máu và bảo vệ gan [1]. Acid coumaric, acid caffeic và acid ferulic là thành phần phenolic chủ yếu trong thân măng tây.…”
Section: Giới Thiệu *unclassified
“…After harvesting, approximately one-third of the lower part of the white asparagus spear is cut off because of its woody texture and to standardize the length of the spears for the market (Zhang et al, 2014). A significant waste stream is thus generated, which could potentially be utilised as a food ingredient, for example in the form of asparagus powder for instant soups.…”
Section: Introductionmentioning
confidence: 99%